Sorghum Crop Husbandry - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This brochure is a guide for effective sorghum crop management, covering crucial topics such as land preparation, optimal sowing and seeding rates, fertilizer application, thinning and weed management. It highlights the importance of pest management, specifically addressing issues related to shoot fly, stem borer and bird control. Additionally, the brochure offers valuable insights into proper harvesting and post-harvest handling to alleviate storage pest risks.